2005
DOI: 10.1300/j052v24n04_06
|View full text |Cite
|
Sign up to set email alerts
|

Diuretic Medication Therapy Use and Low Thiamin Intake in Homebound Older Adults

Abstract: Diuretic therapy (DT) plays a major role in disease management. However, one issue of concern in nutritionally vulnerable elders is that diuretic therapy also increases thiamin excretion, and little attention has been paid to the linkage between DT use and dietary intake of thiamin in this older population. The purpose of this study was to assess the relationship between DT use and dietary intake of thiamin in a randomly recruited sample of 342 homebound older adults. Baseline data, including three 24-hour rec… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
5
0

Year Published

2010
2010
2024
2024

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 8 publications
(5 citation statements)
references
References 29 publications
0
5
0
Order By: Relevance
“…Other large-scale and smaller-scale studies of free-living elderly populations demonstrate significant numbers who have inadequate intake (up to 60 %) ( 61 64 ) , possibly due to more rigorous methodological approaches or biases resulting from the age ranges selected, socio-economic or geographical factors ( 65 ) . Inadequate intake in non-free-living elderly populations is reported to be widespread in industrialised nations: between 33 and 94 % ( 66 70 ) . Where subject age is reported as a continuum, vitamin B 1 intake appears to be negatively correlated with this variable ( 47 , 71 ) .…”
Section: Thiamin (Vitamin B1)mentioning
confidence: 99%
“…Other large-scale and smaller-scale studies of free-living elderly populations demonstrate significant numbers who have inadequate intake (up to 60 %) ( 61 64 ) , possibly due to more rigorous methodological approaches or biases resulting from the age ranges selected, socio-economic or geographical factors ( 65 ) . Inadequate intake in non-free-living elderly populations is reported to be widespread in industrialised nations: between 33 and 94 % ( 66 70 ) . Where subject age is reported as a continuum, vitamin B 1 intake appears to be negatively correlated with this variable ( 47 , 71 ) .…”
Section: Thiamin (Vitamin B1)mentioning
confidence: 99%
“…It also has been reported that possible causes among elderly people with thiamin deficiency diseases were health problems like the over consumption of alcohol, or anamnesis such as diabetes or gastric resection, or the administration of multiple medications (9)(10)(11)(12)(13)(14). In this study, there weren't any significant differences in these items; however, it is necessary to consider the relationship between anamnesis and thiamin deficiency now and hereafter.…”
Section: Discussionmentioning
confidence: 72%
“…In conventional studies, reports show that among elderly people with thiamin deficiency diseases, there are many who have a mal-absorption of thiamin which is caused by overconsumption of alcohol or anamnesis such as diabetes, gastric resection, etc. It has also been reported that one other cause could be the influence of medications for those people who consume various medicinal drugs (9)(10)(11)(12)(13)(14). There are also problems with the lack of nutritional intake like vitamins for elderly people; it has been said that the intake conditions especially for bedridden elderly people or those with dementia are not consistent (15)(16)(17)(18).…”
mentioning
confidence: 99%
“…However, the increased risk of deficiency is not limited to hospitalized patients. An examination of the relationship between diuretic therapy and dietary intake of thiamin in 324 homebound older adults, >60 years, from the North Carolina Nutrition and Function Study, indicated that diuretic users were 2.3 and 4.2 times more likely to have intakes below the recommended dietary allowance and estimated average requirement for thiamin, respectively, compared to nonusers, even after adjusting for sociodemographic and meal pattern variables [ 62 ].…”
Section: Part I: Medications Most Likely To Affect Nutritional Stamentioning
confidence: 99%